Degradation and transformation of extracellular polymeric substances (EPS) and dissolved organic matters (DOM) during two-stage anaerobic digestion with waste sludge. (13th April 2017) - Zhang, Zengshuai; Guo, Liang; Wang, Yi; Li, Fengmin; Zhao, Yangguo; Gao, Mengchun; She, Zonglian
Abstract: Two-stage anaerobic digestion of heating pretreated waste sludge was conducted to evaluate the ability of biogas production and the changing of soluble chemical oxygen demand (SCOD), carbohydrate and protein in extracellular polymeric substances (EPS) and dissolved organic matters (DOM). The changes of volatile fatty acids (VFAs) and NH4 + -N were analyzed. The duration of hydrogen production was 1 day and that of the methane production was 10 days. The highest hydrogen yield of 5.5 ml H2 /g VSS and methane yield of 62.1 ml CH4 /g VSS were obtained. The VSS removal of two-stage anaerobic digestion was 40%. Carbohydrate was the main substrate for hydrogen production and protein in DOM was the main sources for methane production. The structural and functional properties of organics in DOM were evaluated by using three-dimensional excitation-emission matrix (3D-EEM) fluorescence spectroscopy with fluorescence regional integration (FRI) analysis. Moreover, the humification index (HIX) and the fluorescence index (FI) were used to evaluate the humification and DOM source. Highlights: Transformation of substrate during two-stage anaerobic digestion was investigated. Composition and utilization of sludge EPS and DOM were analyzed using EEM with FRI. Humic acid-like organics were accumulated and inhibited the utilization of sludge. HIX and FI value were used to evaluate the humification and DOM source.